Redesain logo Wapand Resto Eduentainment sebagai Corporate Identity untuk meningkatkan Brand Awareness - Birama, Nanda; Martono, Siswo; Riyanto, Darwin Yuwono (Jurnal Art Nouveau, 2017)
Wapand Resto Eduentainment is a company which run in a culinary field with their specialty in Chinese and Javanese cuisine made with halal ingredients. Main dishes which usually used in other menus are chicken, shrimp, fish, squid and beef. Wapand also has a huge area which contain fishing pond, ferris wheel, and boutique. But until now, Wapand Resto Eduentainment doesn’t have corporate identity that represent the company which run in a culinary field as well the promotion media. Wapand’s condition right now doesn’t have a logogram which can represent halal culinary company of Chinese and Javanese cuisine, has different logos in every promotion medias, also using red, black, white and yellow as their color identity. So the effort that cneeds to be done for Wapand to represent their culinary business and to compete in a creative industry right now, is to re-design their company’s logo.                Keywords: Resto, Corporate Identity, Brand Awareness